2008
DOI: 10.1002/bem.20408
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional response of dermal fibroblasts in direct current electric fields

Abstract: During the course of normal wound healing, fibroblasts at the wound edge are exposed to electric fields (EFs) ranging from 40 to 200 mV/mm. Various forms of EFs influence fibroblast migration, proliferation, and protein synthesis. Thus, EFs may contribute to fibroblast activation during wound repair. To elucidate the role of EFs during the normal progression of healing, this study compares gene expression in normal adult dermal fibroblasts exposed to a 100 mV/mm EF for 1 h to non-stimulated controls. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 57 publications
(55 reference statements)
0
52
0
Order By: Relevance
“…62 Jennings et al reported the gene profiling following ES to dermal fibroblasts. 63 While they identified 126 transcripts at a level of 1.4 fold of changes, there is little overlap between their report and this work. In fact, the activation of many important genes such as that of MMP, TIMP, COL, EGF, FGF and many others are first time reported in this work.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…62 Jennings et al reported the gene profiling following ES to dermal fibroblasts. 63 While they identified 126 transcripts at a level of 1.4 fold of changes, there is little overlap between their report and this work. In fact, the activation of many important genes such as that of MMP, TIMP, COL, EGF, FGF and many others are first time reported in this work.…”
Section: Resultsmentioning
confidence: 73%
“…In fact, the activation of many important genes such as that of MMP, TIMP, COL, EGF, FGF and many others are first time reported in this work. 63 Moreover, the ES system used in that experiment was agar bridged electrodes, which may have ion exchange between culture medium and agar bridges and may also This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction. The final published version may differ from this proof.…”
Section: Resultsmentioning
confidence: 99%
“…From early research, electrotaxis has been known to play a profound role in embryonic development, neurogenesis, and wound healing. 1,2 Many different cell types and organisms show electrotactic response to dcEF, including neural stem cell, 3 induced pluripotent stem cells, 4 mesenchymal stem cells, 5,6 fibroblasts, [7][8][9] keratinocytes, 10,11 neurons, 2 and C. elegans. 12,13 The physiological dcEF with strength of tens to hundreds of mV per mm (mVÁmm À1 ) originates from the difference in transepithelial potential (TEP), which is supposedly formed by the differential distribution of ion channels on polarized epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Cells on coverslips were placed cell side down into a stimulation apparatus constructed of Delrin® and assembled with vacuum grease, which minimized the cross-sectional area of the media exposed to current to guard against heat production as described in previous studies [16]. Glass tubes containing a gel consisting of 2% agar in saline served as bridges between stimulation chambers and silver/silver chloride electrodes in saline solution, thereby minimizing contamination of media with electrode products.…”
Section: Methodsmentioning
confidence: 99%